2020
DOI: 10.4204/eptcs.315.9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Walk and Dressed Photon

Abstract: A physical model called dressed photon, a composite system of photons and excitation of electrons in the nano-particles, is effectively used in the realm of near-field optics. Many interesting behaviors of dressed photons are known, especially the rapid energy transfer and the accumulation to singular points, e.g., points with strong dissipation. We propose a new modelling of dressed photons based on quantum walks, especially Grover walks on semi-infinite graphs which we call jellyfish graphs, and show a unive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…From this point of view, this model is equivalent to a quantum walk on a graph. Several studies have also been reported that suggest that dressed-photon phenomena correspond to some stationary solution in a quantum-walk system [8,9].…”
Section: Quantum Master Equationmentioning
confidence: 97%
“…From this point of view, this model is equivalent to a quantum walk on a graph. Several studies have also been reported that suggest that dressed-photon phenomena correspond to some stationary solution in a quantum-walk system [8,9].…”
Section: Quantum Master Equationmentioning
confidence: 97%
“…In the extended Maxwell's equation given in (22), an electrically neutral current (κ 0 ) 2 U µ = (κ 0 ) 2 (λ∂ µ φ) behaves exactly like j µ in the original Maxwell's equation, which shows that the constant κ 0 serves as a fundamental unit, such as the electric charge. Therefore, violation of condition (10) causes gauge symmetry breaking, according to which the CD field extended in step [II] suffers from breakdown of both the gauge symmetry and conformal symmetry in the sense of U ν U ν = 0.…”
Section: Clebsch Dual Fieldmentioning
confidence: 97%
“…We believe that the DP is generated through this pair annihilation of the Majorana field. Since the DP field is basically electromagnetic, once it is generated, its behavior in a uniform environment can be walk models [22][23][24]. Intuitively, however, we can expect that some kind of ζ-function enters here as the carrier to convey the above singularity waves, which explains the observation of ζ-function singularities in the quantum walks.…”
Section: Quantization Of the CD Field And Dp Modelmentioning
confidence: 99%
“…The category algebraic approach will play a fundamental role for the quantum walks on graphs with multiple edges and loops. Quantum walks on graphs have been used in the modeling of the "dressed photon" [43], which cannot be understood without focusing on the off-shell nature of quantum fields [44], i.e., the aspect of quantum fields which cannot be described as the collection of the modes satisfying the on-shell conditions, and quantum walks on categories may become important in quantum field theory in general. They will also connect the QCA approach to quantum fields and other approaches to quantum fields.…”
Section: Prospectsmentioning
confidence: 99%